2020
DOI: 10.1016/j.ssi.2020.115409
|View full text |Cite
|
Sign up to set email alerts
|

Prompt microwave-assisted synthesis of carbon coated Si nanocomposites as anode for lithium-ion batteries

Abstract: Hard carbons derived from glucose and glucosamine are synthesized via microwave-assisted hydrothermal carbonization (HTC) and subsequent pyrolysis treatment to be used as anode materials for lithium-ion batteries (LIBs). Related to the limited lithium ion intercalation to graphite (LiC 6 ) resulting relatively low theoretical capacity (372 mAh/g), silicon is considered as one of the most appealing anode materials for LIBs by exhibiting very high theoretical capacity (3578 mAh/g, based on Li 15 Si 4 ).However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The characteristic Nyquist diagrams of PPAPT and PTO are shown in Figure S9a,b. R1, R2, R3, Q1, Q2, and W components of the proposed equivalent circuit (inset picture in the Figure S9) refer to electrolyte resistance, solid electrolyte interphase, charge transfer resistance, polarization of the surface layer, electrical double layer capacitances, and Warburg impedance, respectively . For pristine PPAPT , EIS data were fitted and found R1 as 5.2 Ω, R2 as 77.6 Ω, and R3 as 47.7 Ω with the total resistance of R total : 130.5 Ω.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic Nyquist diagrams of PPAPT and PTO are shown in Figure S9a,b. R1, R2, R3, Q1, Q2, and W components of the proposed equivalent circuit (inset picture in the Figure S9) refer to electrolyte resistance, solid electrolyte interphase, charge transfer resistance, polarization of the surface layer, electrical double layer capacitances, and Warburg impedance, respectively . For pristine PPAPT , EIS data were fitted and found R1 as 5.2 Ω, R2 as 77.6 Ω, and R3 as 47.7 Ω with the total resistance of R total : 130.5 Ω.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, microwave irradiation is extensively investigated because of its fast reaction rates, energy‐saving property, and simplicity. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, microwave irradiation is extensively investigated because of its fast reaction rates, energy-saving property, and simplicity. [30] The structures and morphologies of the prepared carbonized absorbent cotton fiber were investigated by SEM. SEM images of the carbonized absorbent cotton fiber without any treatment are shown in Figure 3a-c.…”
Section: Electrochemical Measurementmentioning
confidence: 99%
“…For example, the hydrothermal (or solvothermal) method does not affect the properties of the material itself, and the process (equipment) is simple and easy to operate, thus gaining increasing attention recently. The reaction conditions of hydrothermal (or solvothermal) can be easily controlled via simple regulation of parameters such as temperature, time, or addition of surfactants, rendering more possibilities for material design [34–37] . Wang et al [38] .…”
Section: Common Coating Methodsmentioning
confidence: 99%
“…Subsequently, many different composite structures have been developed based on carbon materials, of which the encapsulation structure is a research hotspot that has been confirmed to significantly improve the lithium storage performance of silicon‐based materials [48–51] . Generally, the Si/C composites can be divided into 0D (monodisperse nanoparticles), [34,39,49,52–72] 1D (nanofibers and nanotubes), [35,40,73–80] 2D [graphene (G) sheet], [36,41,81–88] and 3D (graphene shell and porous structure) [38,89–99] material according to the encapsulation structure.…”
Section: Encapsulation Structure Of Carbonaceous Materialsmentioning
confidence: 99%